2018
DOI: 10.1117/1.jmi.5.1.013504
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and validation of the thorax phantom Lungman for dose assessment in chest radiography optimization studies

Abstract: This work concerns the validation of the Kyoto-Kagaku thorax anthropomorphic phantom Lungman for use in chest radiography optimization. The equivalence in terms of polymethyl methacrylate (PMMA) was established for the lung and mediastinum regions of the phantom. Patient chest examination data acquired under automatic exposure control were collated over a 2-year period for a standard x-ray room. Parameters surveyed included exposure index, air kerma area product, and exposure time, which were compared with Lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…5) demonstrate that the additional fat thickness increases the radiation dose by 151 % compared with that of the standard phantom size across all of the xray machines with a statistical significant difference (P=0.002). Comparable results regarding the influence of additional fat thickness on radiation dose were reported in study by Otto et al [32] and study be Perez et al [33]. In our study, the larger size phantom was observed to have both higher IAK and lower IQ compared with that of the standard size phantom.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…5) demonstrate that the additional fat thickness increases the radiation dose by 151 % compared with that of the standard phantom size across all of the xray machines with a statistical significant difference (P=0.002). Comparable results regarding the influence of additional fat thickness on radiation dose were reported in study by Otto et al [32] and study be Perez et al [33]. In our study, the larger size phantom was observed to have both higher IAK and lower IQ compared with that of the standard size phantom.…”
Section: Discussionsupporting
confidence: 74%
“…This might be attributed to the high variability of the technical characteristics of image detector types (CR, DDR and IDR systems) and X-ray generators used between and within hospitals ( Table 1). Several studies concluded that the DR systems can produce images with higher image quality compared with that obtained from CR systems, under similar dose levels [33,34] and this can be attributed to DR having a higher detective quantum efficiency (DQE) when compared with CR [35,36]. It is accepted that CR systems need more radiation, when compared with DR, to obtain a similar IQ and literature has reported that DR systems are significantly better than CR in dose minimisation, with possible dose decreases of up to 75% reported in comparison with the CR [34,37,38].…”
Section: Discussionmentioning
confidence: 99%
“…The CT scan was segmented into soft tissue, muscle, bone, and lung parenchyma. The bronchial tree was replaced with a detailed model obtained from UHR CT of the Kyoto Kagaku Lungman phantom [9]. Voxel size was 0.5 mm isotropic.…”
Section: Deformable Chest Phantom With a Respiratory Motion Modelmentioning
confidence: 99%
“…For current chest imaging applications, only the organs in the thorax region of the RAF phantom have been developed further. Additional modifications included the modeling of a more detailed lung background 10 with bronchial trees, pulmonary arteries, and pulmonary veins [Figs. 1(b) and 1(c)].…”
Section: Realistic Anthropomorphic Flexible Phantommentioning
confidence: 99%
“…Sharpness and noise were quantified using the presampling modulation transfer function (MTF) and the normalized noise power spectrum (NNPS), respectively. These metrics were measured from a Carestream flat panel CsI digital detector with a beam quality of 120 kVp and 9 cm PMMA (i.e., lung equivalent thickness 10 ) at the tube exit. The presampling MTF was measured using a version of the edge technique described by Samei et al 26 A square tantalum edge test object of dimension 50 × 50 mm 2 and 1-mm-thickness was placed at the center of the image receptor and oriented manually to obtain an angle of ∼3 deg between the edge and the detector matrix.…”
Section: Generating Radiographic Images Using a Simulation Frameworkmentioning
confidence: 99%